FAKTOR YANG MEMPENGARUHI SIKAP MASYARAKAT TERHADAP PENCURIAN YANG DILAKUKAN REMAJA DESA JAYA TUNGGAL KEC. TUAH NEGERI KAB. MUSI RAWAS - Eva Susanti (Al-Iqtishad: Jurnal Ekonomi Syariah, 2022)
The object of this research study is "Economic influence on theft by teenagers in Jaya Tunggal Village, Tuah Negeri District, Musi Rawas Regency". With the main issues raised from the phenomenon of the people of Jaya Tunggal Village who are prone to theft, in today's times the economy tends to decline and experience uncertainty so that the problem of theft is detrimental and disturbs peace in a society. Because of this, researchers are interested in conducting research on these issues which are considered very important to study. The main issues include: What factors are the causes of acts of theft in Jaya Tunggal Village, Tuah Negeri District, Musi Rawas Regency. What is the attitude of the community towards acts of theft by youths in Jaya Tunggal village. This type of research is study research (field research) supported by library research (literary study). The research method used is observation, interviews and documents. The data analysis technique is descriptive qualitative then concluded deductively. And finally, after conducting research in Jaya Tunggal Village, Tuah Negeri District, Musi Rawas Regency, it can be concluded that the factors causing the occurrence of acts of theft include children's lack of appreciation of religion, economic factors, parental supervision of their children and education. Regarding the theft that occurred, the community did not accept and really hated it because it was an act that disturbed the peace and disturbed the community, with this the community asked the authorities to give sanctions according to what they had done.